Woodland caribou and forestry in Northern Ontario, Canada - Darby, W. R.; Duquette, L. S. (Rangifer, 1986)
Expansion of logging in remote Ontario boreal forest requires mitigation of effects on woodland caribou. Three examples of caribou-forestry interaction are reviewed. In two, caribou were apparently displaced from peripheral portions of their winter range by logging. In the third, caribou disappeared when exposed to: logging in a central third of their winter range; increased deer density, and; a probable increase in predation. In all cases there is no evidence of human harvest. The literature plus experience in Ontario suggest the following mitigative techniques: protection of winter concentration areas, significant calving areas and traditional migration routes from logging; directing timber harvest to forest stands of least value to caribou; restricting disturbance to one large clearcut in a peripheral portion of range rather than dispersing it over a large portion as several small clearcuts; modified site preparation and regeneration, and; restricted road access. Research is required on the effect of forestry on caribou with and without mitigation, and on causes for effects observed.